Torres Strait Baseline Study : pilot study final report, June 1993 : trace metal concentrations in sediments and selected marine biota as indicator organisms and food items in the diet of Torres Strait Islanders and coastal Papuans - Dight, I. J. (Ian J.), 1948- (Research publication (Great Barrier Reef Marine Park Authority) ;, 1993)
Presents results of a scientific study to establish the spatial extent of trace metal inputs resulting from Fly River (Papua New Guinea) discharge and whether there is evidence of elevated metal concentrations within the Torres Strait; presents data collected and concludes that increases in concentrations appear to be associated with coastal run-off during the monsoon season and to be locally elevated in the northern Torres Strait; makes recommendations about indicator species and future sampling programs, with specific recommendations regarding the need to survey trace metal levels in foods which constitute a significant part of the Torres Strait Islander diet.